“Greening” the National Growth: How Global Green Growth Institute (GGGI) Collaborates with Indonesia in 2014-2020 - Rudiany, Novita Putri; Yesandi, Keista Puti (Insignia: Journal of International Relations, 2023)
With its natural richness, Indonesia is not immune from environmental, economic, and social problems. Indonesia remains facing the problem of greenhouse gas (GHG) emissions and environmental degradation resulting from economic activities caused by business-as-usual (BaU) activities. Therefore, Indonesia has developed a framework for a green growth program for national economic development with the Global Green Growth Institute (GGGI) since 2014. GGGI is an international organization that is specifically concerned about green growth at the global level. The Green Growth Concept was agreed upon at the 2005 Asia Pacific ministerial meetings in Seoul, South Korea. Indonesia also ratified the agreements to implement this green growth concept at the national level. This research elaborates on how GGGI, as a global actor, collaborates with Indonesia to develop the green growth framework. This study uses a descriptive qualitative research method with secondary data collection through literature, which will discuss GGGI's efforts to help implement the green growth program in Indonesia in 2014-2020. The case study is analyzed through the Management Approach, Normative Approach, and Enforcement Approach approaches. Through these three approaches, GGGI has succeeded in assisting Indonesia in implementing green growth in Indonesia in 2014-2020. Some of the programs that have been achieved include the eCBA program, the development of Special Economic Zones (KEK), and the implementation of the legal regulations in force in Indonesia. Keywords: enforcement approach, Global Green Growth Institute (GGGI), Green Growth program, management approach, normative approach